Adapting varieties for intercropped systems in the tropics - Francis, C.A.; Flor Montoya, Carlos A.; Temple, Steven R. (International Center for Tropical Agriculture, 1975)
Current methodologies and selection criteria used to screen and adapt var. for intercropping systems, especially beans/maize associations, in the tropics are reviewed. The overall importance of intercropping systems in the tropics is discussed as well as general plant characteristics useful for these systems. Relevent data taken from the literature are given to illustrate the potential of increasing bush and climbing bean yields in intercropping systems as well as results of expt. showing the effect on yields of intercropping beans/maize. Basic procedures followed at CIAT to screen new var. in beans/maize associations are described for bush beans (monoculture at 350,000 plants/ha and intercropped with maize at 350,000 and 40,000 plants/ha, resp.; beans planted 15 days before maize) and climbing beans (monoculture at 300,000 plants/ha and intercropped with maize at 300,000 and 40,000 plants/ha, resp.). Selection criteria for this breeding procedure are briefly discussed including photoperiod insensitivity, maturity, short and nonlodging plant types, population response, uniformity of flowering and maturity, insect and disease resistance, and yield potential. The final step is on- farm testing of new var. and cultural practices, and an evaluation of their impact on farm income and family nutrition. (CIAT)